Pengaruh pembelajaran online terhadap stress akademik siswa pada masa pandemic covid-19 - Annabilah, Fitri (Maliki Interdisciplinary Journal, 2024)
Academic stress during the cpvid-19 pandemic in 2020 increased, it is not uncommon to find students with high levels of academic stress at that time, several obstacles can cause student academic stress, one of which is not being face-to-face during the learning period. The writing in this article uses the literature review method by using existing ebooks, journals, articles, and theses published on google scholar. This article is used as a guide to life and learning for students and the general public, regarding how to overcome academic stress, this article is not only a guide during the pandemic, but can also be a guide for students and students who are experiencing academic stress.